Relations between infrastructure innovations and tourism spending in developed countries: a macroeconomic perspective - Gavurova, Beata; Belas, Jaroslav; Valaskova, Katarina; Rigelsky, Martin; Ivankova, Viera (Technological and Economic Development of Economy, 2021)
Tourism spending as well as innovations are characterized by great economic value, which emphasizes the need for their research from a macroeconomic perspective. The objective of the research was to assess the significance of the relations between infrastructure innovations and tourism spending in a sample of developed countries. The analytical processes included macroeconomic indicators expressing tourism spending and innovations. The research sample consisted of 36 countries of the Organization for Economic Co-operation and Development (OECD) (2010–2019). The analytical processes were primarily performed using robust panel regression and cluster analysis. One of the most important findings is that innovations in information and communication technologies (ICTs) were dominant in terms of the effects on tourism visitors’ spending. The results showed that innovations in other areas of infrastructure (general infrastructure, ecological sustainability) should not be neglected either. The significant effects of selected innovation indicators showed positive trajectories. As a result, with the strengthening of innovation activities, an increase in tourism spending is expected, which may lead to economic development. It can be assumed that innovation efforts in countries such as Mexico, the Slovak Republic and Turkey could have great potential for improvement. Based on the results, innovations should be considered a part of tourism development strategies, while ICTs play an important role in this issue. It is desirable to support effective tools to increase the number of innovations in tourism. These innovation efforts at the national level may translate into higher tourism spending, which appears to be economically beneficial.